Answer:
a) 24
b) -21.
Explanation:
For question a), we first solve whatever is in the parenthesis, because of PEMDAS.
Our original equation was:
4 (6 + (-3)) + 3 (4)
We get rid of the parenthesis first. 6 + (-3) = 6 - 3 = 3, so we have:
4 (3) + 3 (4)
We can multiply, and then add.
12 + 12 = 24.
For question b), we once again start off with getting rid of the parenthesis. However, within the parenthesis, we still have to follow PEMDAS, meaning that we have to do the multiplication first and the subtraction after.
Thus we have:
-2 (6) + 3(-3)
We can multiply things out and then add.
-12 + -9
= -1 (12 + 9)
= -1 (21)
= -21.